PENGARUH ZIKIR TERHADAP KESEHATAN MENTAL - Muslem Muslem (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2023)
Zikir is one of the means used to remember Allah SWT, to remember His truth, His greatness, and the love and mercy He bestows upon humanity. Through zikir, numerous benefits are obtained in relation to mental and spiritual health for Muslims. Zikir can guide individuals towards the path of piety and help build a healthy soul. This creates a balance between physical and spiritual needs, which can alleviate feelings of anxiety, fear, and address everyday life issues. Zikir also strengthens one's faith. On the other hand, the influence of mental health always focuses on an individual's mental state, whether they have problems or possess a healthy spiritual life. It also emphasizes the overall well-being of individuals, encompassing psychological and physical aspects. Mental health as a discipline addresses how individuals resolve their internal struggles to understand life's challenges and make efforts to maintain a pure soul. This research aims to understand the benefits of zikir for every Muslim, reveal the influence of zikir on mental health, comprehend the essence of mental health, identify various inner symptoms commonly experienced by those facing disturbances in tranquility and mental well-being, and emphasize the influence of religious education in the context of mental health. The research methodology employed is descriptive, which seeks to solve current issues. Based on the findings of this study, it can be concluded that zikir can bring individuals closer to Allah and possess incomparable virtues. In fact, Allah Himself states that the likeness of those who engage in zikir and those who do not is like the difference between the living and the dead. Keywords: Dhikr, mental health